Komparasi Pemikiran K.H. Ahmad Dahlan dan Abdurrahman Wahid (Gus Dur) tentang Pendidikan Humanisme - Pratama, Muh Chaeruddin; , Bapak Dr. Ari Anshori, M.Ag; , Dr. Mutohharun Jinan, M.Ag (2015)
The background of this study is that education today has lost the aspects of human (dehumanization). This happens because the learning method does not provide space for learners to develop according to their potential. Therefore, the subject matter of this discussion is to examine the concept of humanism education of the two figures that have a major influence on the world of education in Indonesia, namely KH Ahmad Dahlan and K.H. Abdurrahman Wahid. Thus this study aims to determine the thought KH Ahmad Dahlan and Abdurrahman Wahid on humanism education. This study is a research library or library research in data collection method using the method of documentation. The approach used by the researchers is the historical approach. While the method of data analysis using descriptive analysis method and comparative method. After conducting the study, researchers found that thinking Wahid Ahmad Dahlan and each has the concept of humanism education, ie education which aims to direct the potential possessed by learners in order for them to become more humane. Both characters have the same rationale, which is rooted in al-Qur'an and al-Hadith \ as a guide to Islamic teachings. It is not independent of the origin of the two who was born in boarding schools. In a further development, the wanderings Ahmad Dahlan and Gus Dur in search of knowledge to many countries, made the two characters have their concept of education. Thus, Ahmad Dahlan and Gus Dur has differences and similarities in the thinking.